Komparasi Algoritma Klasifikasi Dengan Menggunakan Anaconda untuk Memprediksi Ramai Penonton Film di Bioskop - Rano Agustino (Jurnal Teknologi Informatika dan Komputer, 2019)
In the interest of Moviegoers with trendy films,cinemas also play a major role in attracting audiences towatch films they like. But changes that are quite dynamicfrom audience interest take turns, sometimes it issometimes not crowded. Thus sometimes the cinemamanager experiences an error in placing the film to beaired, so the number of viewers in the cinema is not asexpected. From this problem, researchers are interested inanalyzing data relating to film audiences in the cinema.By using CART classification, NBC (Naive BayesClassifier) algorithm, SVM (Support Vector Machine), LR(Logis Text Regression) and LDA (Linear DiscriminantAnalysis) which will be compared which accuracy is thebest for predicting the absence or absence of theaudience. Researchers use Anaconda to compare sixalgorithms and will see the highest results from theConfusion Matrix and ROC Curve